Bergendang dan berpantun dalam Electroacoustic - Dayang Zuridah, Binti. Abang Sharbini. (Universiti Malaysia Sarawak (UNIMAS), 2007)
This is an electroacoustic piece of a traditional membranophone of Gendang Melayu Sarawak and a vocal part, the pantun recital. It is inserted with a narrative of the gendang functions along with the pantun in Sarawak's Malay community as a ritual healing ceremony, entertainment during happy occasions such as weddings, and as an accompaniment to boost fighting spirit of the warrior in 'silat', a Malay self defense art. Through a character creation of the gendang beating dntmmer called as Tukang Gendang, the rhythm was been manipulated and its beauty of the sound was used to narrated his inner emotions and to create an imaginmy atmosphere. The same goes with the pantun recital that was seldom been used long ago by the Malay's community to express their feelings and wants.